Platelet-Rich Plasma in Anterior Cruciate Ligament Quadriceps Tendon Bone Reconstruction—Impact of PRP Administration on Pain, Range of Motion Restoration, Knee Stability, Tibial Tunnel Widening and Functional Results - Konrad Malinowski; Michał Ebisz; Robert F LaPrade; Marcin Mostowy (Applied Sciences, 2021)
Background: Using Platetet-Rich Plasma (PRP) in anterior cruciate ligament reconstruction (ACLR) has been suggested to improve patient outcomes. The aim of this study was to assess the impact of PRP administration on pain, range of motion (ROM) restoration and the functional results of ACLR performed with quadriceps tendon bone (QTB) autografts. Methods: A total of 106 patients were included in this multicenter study. Fifty-two patients underwent single-bundle QTB ACLR and 54 patients underwent the same procedure with additional PRP administration. Results: Mean time of need for on-demand analgesia was 8 days in the PRP group and 11 days in no-PRP group. Symmetric full extension was restored in a mean of 40 days in the PRP group and 53 days in the no-PRP group. Ninety degrees of flexion was restored at a mean of 21 days in the PRP group and 25 days in the no-PRP group. At 18 months postoperatively, the mean side-to-side difference in anterior tibial translation with the use of an arthrometer (Rolimeter, Aircast Europa) was 1.3 mm in the PRP group vs. 2.7 mm in the no-PRP group. Mean tibial tunnel widening was 1.4 mm in the PRP group vs. 2.1 mm in the no-PRP group. The mean score in the pain section of the KOOS scale was 93 in the PRP group vs. 89 in the no-PRP group. For the IKDC scale, 53 patients in the PRP group graded A or B and 1 patient graded C. In the no-PRP group, 48 patients graded A or B and 4 patients graded C or D. Conclusions: The use of PRP in QTB ACLR may decrease the need for on-demand analgesia and accelerate ROM restoration as well as improve knee stability, lessen the extent of tibial tunnel widening and potentially diminish pain at 18 months postoperatively. Further studies will be needed to confirm all authors’ conclusions.